Lost in missions? Employees as a top strategic priority of the world's biggest banks - Dmitry A. Ruban; Natalia N. Yashalova (Journal of Risk and Financial Management, 2021)
Human resources are vitally important to banking. The mission statements of 50 banks with the biggest market value are analyzed qualitatively and quantitatively for subsequent judgments of consideration of employees among top strategic priorities of these organizations. The staff-related notions are found in the only 30% statements. Employees are considered in different aspects, and most frequently in regard to their work and duties. The top 10 banks pay attention to personnel development, career, and success. The findings of the present study indicate on the underrepresentation of the staff-related strategic priority in the mission statements of the world's biggest banks. This seems to be a serious cavity in their strategic communication, dangerous to organization reputation and job satisfaction, and, thus, many actual mission statements need improvement.
Keywords: 330; corporate communication; financial organization; human resources; mission statement; strategic management